Ni-Catalyzed Reductive Carbonylation of Alkyl Halides to Form Dialkyl Ketones Using Diphenyl Oxalate as CO Surrogate - Sun, Yuren; Su, Lei; Tong, Weiqi; Yao, Ken; Gong, Hegui (Synlett, 2021)
In this work, we disclosed that diphenyl oxalate serves as a CO surrogate to enable a Ni-catalyzed carbonylation of alkyl bromides/tosylates to afford dialkyl ketones. The reaction shows broad substrate scope and good functional group tolerance.
Keywords: nickel catalysis; reductive carbonylation; diphenyl oxalate; CO; dialkyl ketone